Enhancing Qur’anic Reading through Tajweed Instruction: A Study of Grade 4 Students at MDTA Al-Falah - Nurohmah, Alfia; Tajul Muttaqin; Dede Supendi (Sinergi International Journal of Islamic Studies, 2025)
Reading the Qur'an correctly and accurately is an obligation for every Muslim. One important aspect of Qur'anic recitation is Tajwid, which ensures the precise pronunciation of letters and adherence to proper articulation rules. However, many students at the Madrasah Diniyah Takmiliyah Awaliyah (MDTA) level still struggle to apply Tajwid rules when reading the Qur'an. This study analyzes the effectiveness of instructional assistance in improving the Qur'anic reading skills of fourth-grade students at MDTA Al-Falah, Desa Neglasari, Kecamatan Darangdan. The research employs a qualitative approach using the Participatory Action Research (PAR) method, which involves direct participation from researchers, teachers, and students in the learning process. The study follows four stages: planning, action, observation, and reflection. Data collection methods include participatory observation, in-depth interviews, and document analysis, while data analysis follows the Miles and Huberman model. The findings show a significant improvement in students' understanding and applying Tajwid rules. Before the intervention, only 40% of students had a basic knowledge of Tajwid, but this number increased to 85% after the assistance program. Students also demonstrated improved fluency in reading the Qur'an and greater confidence and enthusiasm for learning. This study highlights the crucial role of teachers and parents in supporting students' progress. It provides a model that other educational institutions can adapt to enhance the quality of Qur'anic education.